MELESTARIKAN BUDAYA BANYUMASAN MELALUI DIALEK BAHASA NGAPAK - Isrofiah Laela Khasanah; Heri Kurnia (Universitas Warmadewa, 2023)
The Banyumas people, who are popularly called wong Banyumasan, are widely known as unique and different figures compared to other Javanese people. The special difference lies in the accent they use, namely the ngapak language. It is called ngapak because the pronunciation of the vowels